USING TED TALK VIDEO TO IMPROVE STUDENT’S SPEAKING ABILITY IN ELEVEN GRADE STUDENTS AT SMA NEGERI 5 SAMARINDA - Abdul Rohman; Haya Desi Afifah Danu Ado (SISTEMA: Jurnal Pendidikan, 2022)
We can still learn a lot about effective public speaking abilities from TED talks, it can encourage student self-confidence and learn how the body movement, intonation, eye contact and keep awareness without nervous, a student will be able to build up confidence in persuading others more effectively on the ideas and opinion that they would like to share comfortably. Watching TED videos Talks provide an overview of the structure of content, helping to understand the content very well. Also, it can help to learn profoundly and as a new learning model that becomes learning becomes interesting. The purpose of this study is to find out the extent of the effect of using Ted Talk videos in influencing students speaking skills This study uses classroom action research that focuses on only one problem that arises from the natural situation of the classroom. The result shows that the implementation of Ted talk videos can improve the students' speaking skills. The students' score in speaking skills before using the Ted talk video technique was low, with the mean score of the pre-test (55). The percentage of the students who got a point up to 75 grew up in the post-test and the mean is (81).